Implementasi Excellent Service di Madrasah Aliyah Negeri 1 Bandar Lampung - Fakhri, Jamal (Universitas Islam Negeri Raden Intan Lampung, 2017)
This study aims to analyze the ability of MAN 1 in implementing an excellent service in the field of education. Data is collected through (i) interviews, using interview guides in the form of detailed data on questions to be given to the principal, head of administration, administrative staff, curriculum waka, student affairs, infrastructure, community relations, treasurer committee, treasurer expenses, students and librarians. (ii) observation, namely non passive participants. Researchers did not interfere with the school administration's activities as a whole. (iii) Documentary studies, namely methods for finding data through things such as notes, interviews, photographs of administrative activities at school. The results of the documentation study are used as evidence that researchers have carried out research in the field of observation and documentation study. While the results of this study are: The program for improving the quality of education in MAN 1 in general is in accordance with the eight National Education Standards (SNP). Educational quality improvement programs have been formulated even though they are still global in nature.